2021
DOI: 10.3389/fcimb.2021.775554
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells in Response to Intracellular Pathogens: Protection Versus Immunopathology

Abstract: Innate lymphoid cells (ILCs) are a heterogeneous group of cytokine-producing lymphocytes which are predominantly located at mucosal barrier surfaces, such as skin, lungs, and gastrointestinal tract. ILCs contribute to tissue homeostasis, regulate microbiota-derived signals, and protect against mucosal pathogens. ILCs are classified into five major groups by their developmental origin and distinct cytokine production. A recently emerged intriguing feature of ILCs is their ability to alter their phenotype and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 245 publications
(426 reference statements)
0
22
0
Order By: Relevance
“…These results, only revealed through RORγt-Cre fate mapping strategies, highlight the plasticity of intestinal RORγt + ILC3 subsets and their ability to switch from “homeostatic” ILC3s to IFNγ-producing “inflammatory” ex-ILC3s/ILC1s. While the transition of NCR + ILC3s to ex-ILC3s/ILC1s can be pathogenic, this plasticity is dichotomous and may also be beneficial by evoking protective immunity to certain intracellular pathogens through the production of pro-inflammatory cytokines, namely IFNγ that enables the production of mucus-forming glycoproteins to protect the epithelial barrier ( 53 , 93 ).…”
Section: Ilc3 Plasticity In the Gut: Controversial Players Within A C...mentioning
confidence: 99%
“…These results, only revealed through RORγt-Cre fate mapping strategies, highlight the plasticity of intestinal RORγt + ILC3 subsets and their ability to switch from “homeostatic” ILC3s to IFNγ-producing “inflammatory” ex-ILC3s/ILC1s. While the transition of NCR + ILC3s to ex-ILC3s/ILC1s can be pathogenic, this plasticity is dichotomous and may also be beneficial by evoking protective immunity to certain intracellular pathogens through the production of pro-inflammatory cytokines, namely IFNγ that enables the production of mucus-forming glycoproteins to protect the epithelial barrier ( 53 , 93 ).…”
Section: Ilc3 Plasticity In the Gut: Controversial Players Within A C...mentioning
confidence: 99%
“…Innate lymphoid cells (ILCs) are an essential part of innate mucosal immunity. ILCs can sense environmental changes and rapidly respond by producing effector cytokines to limit pathogens spread, initiate tissue recovery, regulate epithelial cell differentiation and activate other immune cells, thereby facilitating inflammatory response [ 3 , 4 , 5 ]. Moreover, recent studies reported that ILCs can regulate the activity of adaptive immune cells through direct cell-to-cell contact and cytokine production [ 3 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transcription factor Eomes controls NK cells differentiation, while T-bet, GATA3 and RORγt are important for ILC1, ILC2 and ILC3 development and their effector cytokine production, respectively [ 13 , 16 ]. Intracellular pathogens and viruses activate ILC1s to produce IFNγ and TNF [ 5 , 17 ]. Along with these effector cytokines, NK cells can mediate cytotoxic activity by releasing perforins and granzymes to induce apoptosis of target cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations